Batteries, Big Red, and Busses - Ashley Boyd; Summer Melody Pennell (Study and Scrutiny)
In this article, a reprint from S&S 1.1, the authors posit the avenue of young adult literature as an untapped resource for cultivating students’ knowledge of social theories and their recognition of societal inequities. Combining specific perspectives of social justice education and young adult literature can be a rich and engaging experience for students, as these contemporary texts afford for multiple layers of analysis. To learn more of the context supporting this work, read Terri Suico’s interview with Ashley Boyd in this issue.